The Quasi-Hyperbolic Tribonacci and Quasi-Hyperbolic Tribonacci-Lucas Functions - Taşçı, Dursun; Azman, Huriye (Communications in Mathematics and Applications, 2014)
In the present paper, we studied an extension of the classical hyperbolic functions. We wrote a new relation that is equal to the Binet formula of the Tribonacci-Lucas numbers. We defined the quasi-hyperbolic Tribonacci and quasi-hyperbolic Tribonacci-Lucas functions. Finally, we investigated the recurrence and hyperbolic properties of these new hyperbolic functions.